Lower Estimates for Certain Harmonic Functions in the Half Space - Gang Xu; Xiaoyu Zhou (Abstract and Applied Analysis)
We will give the growth properties of harmonic functions of order greater than one in a half space, which generalize the result obtained by B. Levin in a half plane.